Institutional and economic determinants of corporate social responsibility disclosure by banks: institutional perspectives - Oliveira, J.; Azevedo, G.; Silva, M. J. (Meditari Accountancy Research, 2019)
Purpose: This article explores the firm and country-level institutional forces that determine banks’ CSR reporting diversity, during the recent global financial crisis. Design/methodology/approach: Specifically, the present article assesses if economic and institutional conditions explain CSR disclosure strategies used by thirty listed and unlisted banks from six countries in the context of the recent 2007/2008 Global Financial Crisis. The annual reports and social responsibility reports of the largest banks in Canada, UK, France, Italy, Spain and Portugal were content analyzed. Findings: Findings suggest that economic factors do not influence CSR disclosure. Institutional factors associated with the legal environment, industry self-regulation and the organization’s commitments in maintaining a dialogue with relevant stakeholders are crucial elements in explaining CSR reporting. Consistent with the Dillard’s et al. (2004) model, CSR disclosure by banks not only stems from institutional legitimacy processes, but also from strategic ones. Practical implications: Findings highlight the importance of CSR regulation to properly monitor managers’ opportunistic use of CSR information and regulate assurance activities (regarding standards, their profession, or even assurance) to guarantee the reliability of CSR information. Originality/Value: The study makes two major contributions. First, it extends and modifies the model used by Chih et al. (2010). Second, drawn on the new institutional sociology, this study develops a theoretical framework that combines the multilevel model of the dynamic process of institutionalization, transposition, and deinstitutionalization of organizational practices developed by Dillard et al. (2004) with the Campbell’s (2007) theoretical framework of socially responsible behaviour. This theoretical framework incorporates a more inclusive social context, aligned with a more comprehensive sociology-based institutional theory (Dillard et al., 2004; Campbell, 2007), which has never been used in the CSR reporting literature hitherto.